Treatment of a cat with presumed Bartonella henselae‐associated immune‐mediated hemolytic anemia, fever, and lymphadenitis. (6th April 2022) - Nivy, Ran; Lavi‐Ginzberg, Yael; de Sousa, Keyla Carstens Marques; Golani, Yael; Kuzi, Sharon; Nachum‐Biala, Yaarit; Harrus, Shimon
Abstract: A 2.5‐year‐old castrated male cat presented with fever and marked generalized lymphadenopathy of 4‐months duration, despite treatment with amoxicillin‐clavulanate/marbofloxacin. Abnormalities were not detected on complete blood count, serum chemistry, and FIV/FeLV test apart from a borderline, non‐regenerative anemia. Peripheral lymph node fine needle aspirations revealed a marked increase in the percentage of intermediate‐ and lymphoblastic‐lymphocytes in addition to reactive macrophages. Three weeks after presentation, the cat developed a severe, regenerative, immune‐mediated hemolytic anemia (IMHA) which responded to immunosuppressive therapy. Fever and lymphadenopathy persisted. Peripheral lymph nodes tested positive for Bartonella henselae DNA in real‐time PCR assay and sequencing. Treatment with pradofloxacin and doxycycline resulted in resolution of clinical signs, and negative PCR tests. Despite its reported low pathogenicity, B. henselae infection should also be considered in cats with protracted unexplained fever, lymphadenitis, and IMHA. Furthermore, a combination of pradofloxacin and doxycycline might be considered in cats with bartonellosis given its apparent clinical efficacy.